Seroprevalence of anti-Helicobacter pylori antibodies in population of Sulaimani governorate/Kurdistan Region/Iraq - Al-Windi, Ahmad; Hussain, Ali Hattem; Salih, Narmin (Sulaimani Journal for Pure and Applied Sciences, 2013)
Helicobacter pylori (H. pylori) infection is one of the most common chronic bacterial infection in the world. Objective: This study was done to assess the extent of H. pylori infection in Suleimani governorate by noninvasive ELISA technique for quantitative detection of anti-H. pylori IgM, IgG and IgA antibodies in serum. Methods: The study included 335 adult and children volunteers from Chamchamal and Sulaimani cities in Kurdistan region / Iraq. The participants answered a structured questionnaire and a blood sample was taken for serological analysis from each participant. The level of serum antibodies for IgM, IgG and IgA were detected using ELISA technique. Results: In the total sample 20.4% had positive IgM, 32.3% positive IgG and 58.2% positive IgA. Two hundred thirty four (74%) subjects had one or more of the antibodies, 138 subjects (41.1%) had at least one antibody positive (IgM 11 (3.2%), IgG 35 (10.4%), IgA 92 (27.4%). In this study 20% had at least two antibodies positive {IgM 25 (7.4%): IgG 45 (13.4%): IgA 64 (19.1%)}. Conclusions: H. pylori infection is common in population of Sulaimani governorate. IgA anti-H. pylori is the most prevalent antibody of population in Sulaimani governorate. The age group of 20-30 years old has the most seroprevalence of antibodies specific to H. pylori.
Keywords: Antibodies; Helicobacter Pylori; IgA; IgG; IgM; seroprevalence